Research on Pathways to Desistance (Maricopa County, AZ and Philadelphia County, PA): Subject Measures - Scales, 2000-2010 - Mulvey, Edward P. ([Verlag nicht ermittelbar], 2017)
The Pathways to Desistance study was a multi-site study that followed 1,354 serious juvenile offenders from adolescence to young adulthood in two locales between the years 2000 and 2010. Enrolled into the study were adjudicated youths from the juvenile and adult court systems in Maricopa County (Phoenix), Arizona (N=654) and Philadelphia County, Pennsylvania (N=700).Respondents were enrolled and baseline interviews conducted from November 2000 to January 2003. Follow-up interviews were then scheduled with the respondents at 6, 12, 18, 24, 30, 36, 48, 60, 72 and 84 months past their baseline interview.The enrolled youth were at least 14 years old and under 18 years old at the time of their committing offense and were found guilty of a serious offense (predominantly felonies, with a few exceptions for some misdemeanor property offenses, sexual assault, or weapons offenses). Each wave of data collection covered six domains: (1) background characteristics (e.g., demographics, academic achievement, psychiatric diagnoses, offense history, neurological functioning, psychopathy, personality), (2) indicators of individual functioning (e.g., work and school status and performance, substance abuse, mental disorder, antisocial behavior), (3) psychosocial development and attitudes (e.g., impulse control, susceptibility to peer influence, perceptions of opportunity, perceptions of procedural justice, moral disengagement), (4) family context (e.g., household composition, quality of family relationships), (5) personal relationships (e.g., quality of romantic relationships and friendships, peer delinquency, contacts with caring adults), and (6) community context (e.g., neighborhood conditions, personal capital, and community involvement). Information about the measures used to capture this information can be found on the Pathways to Desistance website. The current Subject Measures study primarily consists of the calculated scores from constructs asked about during the interview, but the individual scale items were withheld at that time. These variables are typically consistent across the waves that the scale was asked about during the course of the entire study. Most of the files contain variables from all 11 waves of data collection. The table in the front of the User Guide will list which waves are present in each data file.